Gambaran Komunikasi Interpersonal Petugas Pendaftaran Pasien Terhadap Kepuasan Pelayanan di Puskesmas Karang Pule - Syamsudin; Ria Rahmatul Istiqomah; Heru Purnama (ARTERI : Jurnal Ilmu Kesehatan, 2019)
Interpersonal communication is communication that occurs between two or more, which is usually not formally regulated. Satisfaction of health services is achieved if what the patient gets exceeds his expectations. The design of this research is quantitative descriptive that aims to see the picture of patient satisfaction can further improve the quality of service. The variables of this study were patient satisfaction with services in Karang Pule Health Center in Mataram City which included registration counters with subvariables of empathy, openness, equality and support. To identify the level of patient satisfaction with the service process by the patient registration officer at the Karang Pule Health Center in MataramCity, based on 4 interpersonal communication attitudes namely empathy, openness, equality and support. To find out the picture of interpersonal communication on patient satisfaction at the service at Karang Pule Health Center, Mataram City.This research method is quantitative descriptive is a scientific observation and is carried out carefully and carefully so that the results are more accurate and precise. The study population was visitors to the Karang Pule Health Center in Mataram City in December 2018. The sampling method was using the Slovin formula. Samples were taken 97 patients in PuskesmasPularang, Mataram City. Data analysis techniques used a cross sectional approach. The conclusion of the research conducted Karang Pule Puskesmas showed that the quality of services provided by the Puskesmas was saticsfactory.